SISTEM JUAL BELI ONLINE DI SUPPLIER HERBAL MURAH SURABAYA PERSPEKTIF AKAD AL-SALAM - Muhammad Amru Rahman (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
The modern world can not be separated from Interconnectted network (internet). Similarly, in bermuamalah. Commercial business over the Internet is known as electronic commerce. Internet merge into a worldwide computer network system information. The Internet allows the practice bermuamalah without any real meeting between the perpetrators. Surely this is an opportunity for businesses. The time will be more efficient. The perpetrators can perform transactions anytime and anywhere. In addition to being profitable can also cause problems. Especially legal issues. Besides, it was also the problem of incompatibility of information with reality, either on-time delivery and choice of goods. Cheap herbal supplier is a provider of herbal medicine who also use the internet to sell his wares to al-sala>m. Customer view a selection of items offered via the internet. Then he did some communication with suppliers to place the goods.